Fostering social mobility. The case of the Bono de Desarrollo Humano in Ecuador. Issue 4 (2nd October 2021) - Mideros, Andrés; Gassmann, Franziska
ABSTRACT: Social protection programmes are now expanded due to their efficacy in reducing poverty and vulnerability. However, the literature is scarce regarding long-term effects. Using administrative panel data, this study analyses social mobility in Ecuador and evaluates the effect of the social transfer programme Bono de Desarrollo Humano (BDH). Results show that social policies should focus on household composition, the accumulation of human capital, and the accumulation of durable goods. Complementary policies must address gender and ethnic equity, as well as reproductive health. Finally, we find that the BDH does foster social mobility, especially if the transfer is complemented with economic inclusion programmes.